Describe the documents from the search for the word to search for meaning - Giorgio Poletti (Je-LKS: Journal of E-Learning and Knowledge Society, 2012)
The article aims to reflect, as much organic as possible, the relationship that has arisen between the applications of semantic web and educational technology. The choice set according to this line of work has as its origin the need, which seems crucial to think, ten years after the birth of the "Semantic Web Initiative" is a changed methodology by which information is shared on the network and whether these changes induce a real added value to educational technology by evolving their methodologies. The document with which the group of "Semantic Web Initiative" aimed to define their work says that "the goal of the Semantic Web is the Web the same: create a universal medium for data exchange", the universality of a support data exchange, but even better information must be based on a description logic that makes content "device independent". Only a real logic of semantic cataloging of documents will enable the application of semantic web to support the methodologies related to educational technology in recurrent dialogue with the evolution of the web. The ultimate goal is to see how educational technology, to benefit from applications of the Semantic Web is to provide tools for understanding and disambiguation of concepts to achieve shared documents that are "machine readable" to give answers to questions that users cannot make.